Novelties in Brachystele Schltr. (Orchidaceae, Orchidoideae): a new synonym and a lectotype, including notes on geographic distribution, phenology, relationships and conservation status - Dos Santos, Igor Soares; Da Silva, Marcos José (Phytotaxa, 2024)
During taxonomic studies on the species of Brachystele Schlechter occurring in Brazil, we provide here the typification of B. subfiliformis (Cogniaux) Schlechter, a species endemic to Brazil, and we also propose B. bicrinita Szlachetko under its synonym. Therefore, we provide the updated geographic distribution of B. subfiliformis, its conservation status, images, and comments regarding its environmental preferences, phenology, and morphological relationships.